(3GdCUhd GdYdejIs - (3eMeO GdcQeGfjs ((3eMeO Hf Ydj GdNhfSGQjs)
(3ChdgG (B:s
(3Gdbhd aj GdCUhd GdYdejI hgj YHGQI Yf GdhXGFa GdebQQI hGdbhGYO GdeYJHQI GdJj jSJQjM Gdecda HgG YfO GdMjQI(B...s
(3BNQgG (B:s
(3adh MGhd GdeYJHQ ef GYJHGQ YOe GdVQQ Pdc adG hLg ddGbJUGQ Ydjg Hd jYJHQ ajg HgPG GdeYfi Cf dG jbhe Ydi NdGagG Odjd GLJgGOj eJcad ddMce GdaYdj(B. (3gPG BNQ EKHGJg aj gPG GdeLGd(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 769s
(3GdPQjYI HQbe(B: 769s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs